EVALUASI PELAKSANAAN PROGRAM PENGENDALIAN PENYAKIT DEMAM BERDARAH DENGUE (DBD) - Irawan, Suma (Jurnal Ilmu Administrasi Negara, 2017)
Abstract: Evaluation of Program Implementation Control of Dengue Haemorrhagic Fever(DHF). This study aimed to evaluate the Program Implementation Control of Dengue Feverand inhibiting factors. This research type is descriptive research with qualitative approach. Informantsin this study are the people who play a role in the program Implementation Control ofDengue Haemorrhagic Fever (DHF) in the District of Pangkalan Kerinci, Pelalawan. The techniqueof collecting data using interviews, observation and documentation. Deskriptif data analysisis qualitative. The results of this study concluded that the implementation of disease controlprograms of dengue hemorrhagic fever (DHF) in the District of Pangkalan Kerinci Pelalawanseen from indicators of effectiveness, efficiency, adequacy, equity, responsiveness and accuracyare still many shortcomings. None of the evaluation indicators used can be fulfilled in the implementationof disease control programs of dengue hemorrhagic fever (DHF) in the District ofPangkalan Kerinci, Pelalawan.